SISTEM PAKAR MENDETEKSI PENYAKIT ASMA PADA PUSKESMAS LINGKAR TIMUR BENGKULU - Asnawati, Asnawati; Bendrianti, Rita Prima; yono, Hari Aspri (UNIVED Press, 2013)
Expert system detection of asthma. This research aims to create an expert system application detection asthma in eastern rim Bengkulu clinic using Visual Basic 6.0 programming language in knowing gelaja and without medication should consult with relevant doker or midwife to make the diagnosis of a patient.Data collection methods used in the making of this observation, library research and interviews, the results of research conducted, it can be concluded that the detection expert system asthma in eastern rim centers using Visual Basic 6.0 programming language can improve the performance of the health center east rim Bengkulu